PROGRAPH: A FRIENDLY TOOL FOR MICROCOMPUTER SOFTWARE ENGINEERING - Pietrzykowski, Tomasz; Matwin, Stanislaw; Muldner, Tomasz (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF